Performance improvement in six‐phase symmetrical induction motor by using synthetic voltage vector based direct torque control. Issue 11 (20th May 2019) - Sharma, Sohit; Aware, Mohan; Bhowate, Apekshit; Levi, Emil
Abstract : In this paper, direct torque control (DTC) scheme for a symmetrical six‐phase induction motor by incorporating five‐level torque comparator is presented. The five‐level torque comparator in DTC provides the benefit of torque ripple reduction, compared to a three‐level torque comparator. Adoption of five‐level torque comparator generates the flux in xy ‐subspace which leads to flow of increased stator current. The xy ‐subspace flux is also not responsible for torque production. The synthetic voltage vectors are therefore developed to minimise the xy ‐subspace flux and thus improve performance of the symmetrical six‐phase induction motor. The comparative analysis of the developed switching schemes is presented. The common mode voltage of the drive is also taken care of by the proposed switching scheme. Experimental results are provided to verify the proposed scheme.